PENERAPAN TERAPI MADU MENGGUNAKAN METODE MOIST WOUND HEALING PADA KASUS DIABETIC LEG ULCER DI WILAYAH KERJA PUSKESMAS MASOHI - Ohorella, Usman Barus; Lewenussa, Rupaida; Achmad, Irhamdi; Khair, Andi Miftahul; Metekohy, Feby Adolf (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2023)
Background: Diabetic leg ulcer is a chronic injury caused by peripheral neuropathy and repetitive pressure that results in tissue damage to part or all of the leg area under high pressure. To overcome this, treatment is needed with the application of honey as part of the Moist Wound Healing method. Moist Wound Healing is a wound care method with moist principles that can support cells in the wound healing process. Objective: to see the effectiveness of honey in the Application of Wound Care Procedures Using the Moist Wound Healing Method in Diabetic Leg Ulcer Cases. Method: case study design with descriptive design. Respondents consisted of 2 people who had met the criteria of the researcher. Results: there was a decrease in the REEDA score (Redness, Edema, Ecchymosis, Discharge, Approximation) of respondent 1 from the score (5) to (2), respondent 2 from the score (5) to (2), with an average decrease of 66%. With the state of the ulcer, there is no odor, or exudate, as well as the presence of tissue granulation. Conclusion: the moist wound healing method with honey is effectively used in the treatment of diabetic ulcers. Keywords: Diabetic Leg Ulcer, Wound Care, REEDA, Moist Wound Healing